Visualizable Mathematical Structures: A Framework for Evaluating Mathematical Representation in Computer Graphics - Papadopoulos, Evanthios; Kougias, Ioannis (European Scientific Journal, ESJ, 2026)
The relationship between abstract mathematical structures and their graphical representation constitutes a fundamental problem in computer graphics. This paper examines the criteria that allow a mathematical structure to be transformed into a visual form while preserving its intrinsic properties. Emphasis is placed on geometric interpretation, computational realizability, and structural stability. Drawing on principles of vector geometry and spatial modeling, a coherent framework is proposed to identify visualizable structures. The paper further incorporates mathematical examples and schematic descriptions to clarify the transition from formal definition to graphical representation. The results contribute to both theoretical understanding and practical modeling methodologies.